Consistency in reporting sensitive sexual behaviours in Britain: change in reporting bias in the second and third National Surveys of Sexual Attitudes and Lifestyles (Natsal-2 and Natsal-3). (25th November 2013) - Prah, Philip; Copas, Andrew J; Mercer, Catherine H; Clifton, Soazig; Erens, Bob; Phelps, Andrew; Tanton, Clare; Sonnenberg, Pam; Macdowall, Wendy; Wellings, Kaye; Johnson, Anne M
Abstract : Objectives: Britain's second National Survey of Sexual Attitudes and Lifestyles (Natsal-2) was conducted in 1999–2001 and the third (Natsal-3) was conducted in 2010–2012 to update prevalence estimates of sexual behaviours and assess changes over time. We investigated whether there was a change in reporting bias between these two cross-sectional surveys. Methods: We analysed data from the 'common birth cohort' of participants born during 1956–1983, who were eligible to take part in Natsal-2 (n=10 764) and Natsal-3 (n=6907). We compared estimates for outcomes that occurred before Natsal-2 and expected these to be consistent between surveys if no change in reporting bias had occurred. Results: A greater proportion of non-white men and women were in Natsal-3 consistent with demographic changes in Britain. Reporting behaviours was largely consistent between surveys for men. Fewer women in Natsal-3 reported early first intercourse or having child(ren) before age 20; they were also more likely to report not discussing sex with their parents at age 14. Men and women in Natsal-3 were more likely to report tolerant attitudes towards same-sex partnerships but less tolerance towards unfaithfulness in marriage and one-night-stands. Conclusions: We found little evidence of change in reporting bias among men since Natsal-2. Among women, a modest change in reporting bias was observed for a small number of experiences, possibly due to changes in participation, social acceptability and methodological differences between surveys. Changes in the reporting of sexual behaviours and attitudes over time observed in the wider Natsal-3 study are therefore likely to largely reflect real changes in the population.